Empathy as a Tool for Embodiment Processes in Vocal Performance - Heisel, Erin (Empirical Musicology Review, 2015)
One way of understanding empathy in music performance is as a process by which singers closely identify with the characters they encounter and portray in opera or art song. As singers embody these characters, they literally give them voice. Musical performance thus humanizes characters as well as performers and audiences as deeper, empathetic engagement may also reflect or elicit new pathways of growth, knowledge, and understanding. What is the process a singer goes through in empathizing with a character? How can young singers learn to empathize with the characters they are tasked with portraying, even when they may find the characters or their behavior to fall outside of their own moral convictions? This paper posits that empathy is a necessary part of the role preparation process for singers and introduces the “role journal” as a way for young singers to track embodiment processes and develop healthy habits of empathy and boundaries in their work.